Peningkatan Motivasi Dan Prestasi Belajar Materi Sengsara Dan Wafat Yesus Menggunakan Pembelajaran Discovery Learning Pada Siswa Kelas VIII di SMPN 5 Katingan Hilir - Nurli Aknes Pardosi (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Learning that integrates literacy abilities, knowledge skills, skills and attitudes, as well as mastery of technology is 21st century learning. The characteristics of 21st Century learning are learning that must prepare the generation for advances in Information and Communication Technology (ICT or ICT) which are developing very quickly. These technological developments affect various aspects of life, including the learning process. 21st century learning is integrated with the independent curriculum, the development of which is a further step in developing the 2013 curriculum. At the junior high school level there are still students who lack motivation to study Catholicism. In particular, when presenting material or subjects about the Passion and death of Jesus in Class VIII, SMPN 5 Katingan Hilir, Katingan Regency, Central Kalimantan, from year to year there are always students who experience difficulties in learning so that learning outcomes do not match the expectations of the standards that have been set. . The assessment of Catholic Religious Education and Character at SMPN 5 Katingan downstream is expected to achieve a minimum good attitude score, a minimum knowledge score of 75, and a minimum skills score of proficient. To achieve the goals mentioned above, a learning approach that is quite challenging for teachers is the project-discovery learning approach. Learning Catholicism in schools apart from developing faith education, also has the function of forming good personality or character. Therefore, a learning model that is student-oriented is needed, so that they are able to develop critical thinking skills and solve problems faced in everyday life. Discovery Learning is a learning model that can be applied to independent curriculum history learning because it can encourage students to think critically, have problem solving skills, connect knowledge about problems and real world issues. Based on the description above, it is hoped that this classroom action research can increase motivation and learning achievement in Catholic Religious Education Subjects. The use of the Discovery Learning Model that matches the syntax in learning Catholic Religious Education in class VIII of SMP Negeri 5 Katingan Hilir, material or subject matter about the Passion and death of Jesus, is very effective in increasing student motivation and learning achievement, which can be seen from the pre-cycle student learning motivation in the good category was 40%, increased in cycle I by 73.33% and in cycle II increased by 90%. The increase in student learning achievement can be seen through the average post test score in the first cycle stage, namely 77, then an increase to 89 in the second cycle post test. The improvement looks significant for students who need attention and guidance from teachers and classmates. This can be seen from students who increased quite high by 8%.